Heme and HO-1 Inhibition of HCV, HBV, and HIV - Schmidt, Warren N.; Mathahs, Mary M.; Zhu, Zhaowen (Frontiers in Pharmacology, 2012)
Hepatitis C virus, human immunodeficiency virus, and hepatitis B virus are chronic viral infections that cause considerable morbidity and mortality throughout the world. In the decades following the identification and sequencing of these viruses, in vitro experiments demonstrated that heme oxygenase-1, its oxidative products, and related compounds of the heme oxygenase system inhibit replication of all 3 viruses. The purpose of this review is to critically evaluate and summarize the seminal studies that described and characterized this remarkable behavior. It will also discuss more recent work that discovered the antiviral mechanisms and target sites of these unique antiviral agents. In spite of the fact that these viruses are diverse pathogens with quite profound differences in structure and life cycle, it is significant that heme and related compounds show striking similarity for viral target sites across all three species. Collectively, these findings strongly indicate that we should move forward and develop heme and related tetrapyrroles into versatile antiviral agents that could be used therapeutically in patients with single or multiple viral infections.